Comparison of hemoglobin level measurement results using sodium lauryl sulphate with Oshiro and Mansoor procedure - Fadhilah, Wasiyah Khusna; Al Badri, Muhammad Hilal; Wahid, Aziz Ansori; Fadhila, Feldha (Asian Journal of Health and Applied Sciences, 2022)
The method of measuring Hb levels recommended by ICSH uses the HiCN method. However, it has a high risk due to the toxicity of the reagent. Therefore, the determination of Hb has been developed using the SLS method. According to Oshiro and Mansoor, who both stated that there was no significant difference between SLS and HiCN, this method has two distinct procedures. This study aims to determine the comparison between the measurement results of hemoglobin levels using sodium lauryl sulfate with the Oshiro procedure and Mansoor. The research design used is analytical research. The data obtained from the results of measuring Hb levels with the Oshiro and Manshoor procedures was given to students of the Diploma IV Study Program of Medical Laboratory Technology, Rajawali Health Institute batch 2018, which collected 49 people. The sampling technique used was saturated sampling to reduce the error rate in the study. The results of the normality test of the data in this study showed n of the two procedures was 49 mean±SD for the Oshiro procedure 13.09±0.56 and p = 0.200. Meanwhile, the Mansoor procedure had a meanSD of 13.09±0.57 and a p-value of 0.059. Because the probability of both being p > 0.05, the data is declared normally distributed. The results of the average difference test from the data of this study show the mean±SD of the pairwise difference between the Oshiro and Mansoor procedures is 0.002±0.059 and the p value = 0.811. If P > 0.05, then it is stated that there is no significant difference between the two groups. The conclusion of this study is that the result of measuring Hb levels using the SLS procedure is reliable. Oshiro and Mansoor conform to HiCN and there is no significant difference in the mean results.